Strategi Affiliate Marketing pada Sistem Informasi Penerimaan Calon Mahasiswa Baru - Emanuel Safirman Bata (JITU : Journal Informatic Technology And Communication, 2023)
The high level of educational development in Indonesia, especially in East Nusa Tenggara, spurs every university to continue to innovate to provide the best information technology-based services quickly and easily. Universities that have fast and easy services are one of the attractions for prospective new students to join the college. One of the strategies used to increase the number of new prospective student admissions is to use digital media that handles the registration process. In addition, implementing an affiliate marketing strategy to expand the network and promotional reach. Each affiliate is given a commission in the form of cashback and a regular honorarium every semester for affiliate students who successfully register and actively study at STIKOM Uyelindo Kupang. This will certainly attract many actors to join as affiliates. The performance of affiliate marketing can be seen from the increase in the number of new students by 21% from the previous year which has not implemented an affiliate marketing strategy.